Pengaruh Budaya Organisasi terhadap Kinerja Pegawai Kantor Pelayanan Pajak Madya Denpasar - Tri Wandana, Novan (CITIZEN CHARTER, 2017)
ABSTARCT Organizational culture is an important contributing factor to the success or failure of the company. Culture can be a positive or negative force, in relation to the effectiveness of the achievement of the organization concerned. High performance is the result of cultural consistency. Tthis study has a purpose to know how far the influence of organizational culture on employee performance Tax Office (KPP) Madya Denpasar. The research method used is quantitative method with the intention to seek the influence of organizational culture on employee performance at KPP Madya Denpasar by using correlation approach. Primary data in this observation is questionnaires to 50 employees at Denpasar Tax Service Office. The results showed that organizational culture has a positive effect on employee performance in Denpasar Tax Service Office with R2 result of 0,606, which means that employee performance is influenced by organizational culture equal to 60,6%. Keywords : Organizational Culture, Employee Performance, KPP Madya Denpasar.